Yehorova O., Turysheva O., Koval T. Translation Approaches to Secondary Anthroponymic Nominations (Case Study of B. Obama’s and D. Trump’s Nicknaming). - Yehorova O. I.; Turysheva O. O.; Koval T. Yu. (Philological Treatises, 2020)
The study focuses on translating Barack Obama’s and Donald Trump’s secondary nominations. It suggests an inventory of techniques relevant to the translation of proper names and nicknames in particular. The analysis of open data on the Web exposed a limited number of cases of applying interlingual translation for rendering Barack Obama’s and Donald Trump’s nicknames despite the fact that the politicians have been assigned many during the terms of their office. Alongside, the analysis proved that the second life in other cultural spaces obtain only those bynames that had managed to gain the attention from the wider public, in particular, through a vast media coverage. Among the most widely used methods of translating the politicians’ nicknames, the techniques of transliteration, transcription, calquing, half-calquing, substitution, and descriptive translation prevail. The translator’s goal is not only to apply the relevant translation strategy, but also to preserve the meaning and pragmatics of the original naming embedded by its author. Moreover, an adequate interlingual translation requires the translator to choose a method that would guarantee recognizability of the nickname regardless of the context. However, sometimes, traditional methods of translation lack sufficiency which requires turning to alternative approaches and triggering the translator’s creative potential. In such cases, translator’s virtuosity and linguo-creative skills would enable representing the fragments of the original (source) linguo-cultural space, preserving the implanted concept, as well as rendering both connotation and esthetic functions of the onyms in the target language. Thus, the article introduces the results of examining the existing translation solutions and provides with the authors’ own solutions along with their grounding.